Professional development of academic library professionals in Kerala / Susan Mathew K, Baby, M.D, and Sreerekha Pillai S - Mathew K, Susan; M.D, Baby,; Pillai S, Sreerekha (2011)
The paper aims to bring out the problems and prospects of the professional development opportunities of academic library professionals in the Universities in Kerala. The study is a part of research undertaken to survey the professional development activities and educational needs of library professionals in the major Universities of Kerala because of the developments in Information communication technology. The study recommends methods for improving the knowledge/skills of library professionals. The aim of the study is to evaluate the professional development activities of Library professionals and their attitude towards continuing education programmes. In order to achieve the objectives of the study a survey was conducted with the help of structured questionnaires distributed to 203 library professionals in seven major universities in Kerala, (South India) of which 185 questionnaires were returned. Results of the analysis show that majority of the professionals have pursued higher degrees in library science or IT allied courses after entering the profession, and that they have a positive attitude towards participation in training programmes and workshops. The results show that developments in ICT have a positive influence on majority of library professionals‘ attitude towards continuing education programmes.